2015
DOI: 10.1177/0886260515605124
|View full text |Cite
|
Sign up to set email alerts
|

Circumstances Preceding Homicide-Suicides Involving Child Victims: A Qualitative Analysis

Abstract: Homicide-suicide incidents involving child victims can have a detrimental impact on survivors of the violence, family members and friends of the decedents, and other community members, but the rare occurrence of these acts makes using quantitative data to examine their associated antecedents challenging. Therefore, using qualitative data from the 2003-2011 National Violent Death Reporting System, we examined 175 cases of homicide-suicide involving child victims in an effort to better understand the complex sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 45 publications
3
28
0
4
Order By: Relevance
“…This finding is supportive of previous research that found that women who commit filicide were more likely to have a mental disorder than their male counterparts (Flynn et al 2013;Palermo 2002). While maternal filicide is commonly attributed to severe mental illness (Alder and Polk 2001;Barnett 2006;Flynn et al 2013), the fact that half of the women did not report a mental/emotional problem is notable and consistent with previous studies (Alder and Polk 2001;Holland et al 2015;Porter and Gavin 2010;Stroud 2008). This finding could reflect the fact that offenders with serious illness may be confined in mental institutions and not prisons, and as a result be excluded from the sample.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is supportive of previous research that found that women who commit filicide were more likely to have a mental disorder than their male counterparts (Flynn et al 2013;Palermo 2002). While maternal filicide is commonly attributed to severe mental illness (Alder and Polk 2001;Barnett 2006;Flynn et al 2013), the fact that half of the women did not report a mental/emotional problem is notable and consistent with previous studies (Alder and Polk 2001;Holland et al 2015;Porter and Gavin 2010;Stroud 2008). This finding could reflect the fact that offenders with serious illness may be confined in mental institutions and not prisons, and as a result be excluded from the sample.…”
Section: Discussionsupporting
confidence: 90%
“…According to the Supplementary Homicide Reports data for the years 1990-2004, a total of 2976 maternal filicides were reported in that 15-year period. In addition, this study was unable to include cases of murder-suicide (Alder and Polk 2001;Holland et al 2015) or cases in which the offender is confined in a mental institution. Moreover, important differences could exist in cases of maternal filicide that ended at an earlier point in the criminal justice process, for example, charges were not filed or convictions were not obtained as compared to cases in which offenders were ultimately imprisoned (Scott and Fleming 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Scholars also generally have agreed that homicide-suicide shares a common set of risk factors with intimate partner homicide and family homicide (Haines, Williams, & Lester, 2010;Heron, 2017;Manning, 2014;Salari & Sillito, 2016). Most notably, these acts typically involve a history of interpersonal conflict (Kalesan, Mobily, Vasan, Siegel, & Galea, 2016); occur in suburban and rural locales; involve greater proportions of female, child, and White victims; and include multiple victims (Holland, Brown, Hall, & Logan, 2018;McPhedran et al, 2015).…”
Section: Individual-level Correlates Of Homicide-suicidementioning
confidence: 99%
“…Fathers strangle, shoot, and stab and may kill their spouse, other unrelated children, and even family pets, resulting in them being termed “family annihilators” . Children with disabilities such as autism may be at risk, particularly if the parent has mental illness . Suicide after infanticide is uncommon in most countries, involving only 2.3% of mothers, although the incidence is higher in Japan .…”
Section: Discussionmentioning
confidence: 99%